1990
DOI: 10.1177/0148607190014005437
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Energy Metabolism with Biosynthetic Human Growth Hormone in Patients on Full Intravenous Nutritional Support

Abstract: Our objective was to examine the effect of biosynthetic human growth hormone (BSHGH) on protein and energy metabolism in patients on full intravenous nutrition (IVN). Fifteen patients who had been established on IVN were allocated at random to receive either BSHGH (0.1 mg/kg/day) or placebo daily for 7 days. All patients received the same feeding regimen which contaminated 14 gN, 1000 kcal of glucose and 1000 kcal of fat (Intralipid) daily. The mean nitrogen balance for days 4 to 7 was significantly more posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The results of this study demonstrated that the effect of IGF-I on nitrogen balance could be recognised within 1 day under normoxic conditions, while it required 2 days under hypoxic conditions. In contrast, a positive nitrogen balance after 1 week of treatment with IGF-I was reported in a previous human study [25].…”
Section: Discussionmentioning
confidence: 53%
“…The results of this study demonstrated that the effect of IGF-I on nitrogen balance could be recognised within 1 day under normoxic conditions, while it required 2 days under hypoxic conditions. In contrast, a positive nitrogen balance after 1 week of treatment with IGF-I was reported in a previous human study [25].…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, we think that the lack of functional benefit observed in our study is probably not due to an insufficient increment in IGF-1 levels. The duration of the treatment does not seem too short in our study, as a positive nitrogen balance is known to occur already after 1 wk of treatment (37). Thus, although nitrogen balance was not measured in our study, it is likely that our patients treated by rhGH presented a positive nitrogen balance, as suggested by the increase in lean body mass.…”
Section: Possible Mechanisms Underlying the Observed Effectsmentioning
confidence: 74%
“…Recent studies with recombinant growth hormone have shown that supraphysiological doses promote positive nitrogen balance in many groups: patients with burns,'0 postoperative patients," 12 the critically ill,'3 those with chronic lung disease,'4 those receiving parenteral nutrition,'5 16 and healthy volunteers treated with steroids. " The daily dose of growth hormone used in these studies was 0-12-0-40 U/kg body weight, equivalent to two to five times that used to treat growth hormone deficiency.…”
mentioning
confidence: 99%